El acceso a internet como derecho humano con alcance socio-colectivo (2024)
[Purpose] The article intends to determine if Internet access can be considered as a Human Right according to the postulates of the constitutional generations currently provided for in the Colombian Political Constitution of 1991. [Methodology] The research embraces a critical hermeneutic approach, based on qualitative methods whose main strategy for collecting information is documentary review. [Findings] Human rights currently have an anti-formalist scope, which implies that they do not correspond to exhaustive lists, but rather that from daily reality they can be declared continuously. Such is the case of Internet access, which was not initially provided for in the written norms on human rights but which does represent a requirement from everyday life. This leads to the fact that since the constitutionalization of human rights in the current Colombian legal system, it is considered that it is a right of a complex nature that has second and third generation elements. This leads to the proposal that Internet access is a socio-collective right, which requires criteria of affordability, accessibility, acceptability and adaptability for its materialization. [Practical Implications] A hermeneutic framework is established to understand Internet access as a human right on which the possibility of legally demanding it proceeds. [Originality] From the current Colombian legal system, access to the Internet is not contemplated as a Human Right, for which a disruptive interpretation is proposed from the iustheory of anti-formalism to interpret daily reality from a new constitutional criterion.